Characterization of LiCoO2 Nanopowders Produced by Sol-Gel Processing. (21st September 2010) - Soltanmohammad, Sina; Asgari, Sirous
Abstract : LiCoO 2 nanopowders, one of the most important cathode materials for lithium-ion batteries, were synthesized via a modified sol-gel process assisted with triethanolamine (TEA) as a complexing agent. The influence of three different chelating agents including acrylic acid, citric acid, and oxalic acid on the size and morphology of particles was investigated. Structure and morphology of the synthesized powders were characterized by thermogravimetric/differential thermal analyses (TG/DTA), X-ray diffraction (XRD), and transmission electron microscopy (TEM). Results indicate that the powder processed with TEA and calcinated at 800 ∘ C had an excellent hexagonal ordering ofα -NaFeO 2 -type (space group R3 ¯ m). Also, the other three complexing agents had a decisive influence on the particle size, shape, morphology, and degree of agglomeration of the resulting oxides. Based on the data presented in this work, it is proposed that the optimized size and distribution of LiCoO 2 powders may be achieved through sol-gel processing using TEA as a chelating agent.